Haemostatic therapy in spontaneous intracerebral haemorrhage patients with high-risk of haematoma expansion by CT marker: a systematic review and meta-analysis of randomised trials. Issue 2 (1st April 2021) - Nie, Ximing; Liu, Jingyi; Liu, Dacheng; Zhou, Qi; Duan, Wanying; Pu, Yuehua; Yang, Zhonghua; Wen, Miao; Sun, Haixin; Wang, Wenzhi; Sun, Shengjun; Gu, Hongqiu; et al.
Abstract : Background and purpose: Current randomised controlled trials (RCTs) showed an uncertain benefit of haemostatic therapy on preventing haematoma expansion and improving the outcome in patients with intracerebral haemorrhage (ICH). This meta-analysis aims to systematically evaluate the effect of haemostatic agents on the prevention of haemorrhage growth in patients with high-risk spontaneous ICH predicted by CT signs in RCTs. Methods: A comprehensive search of PubMed, EMBASE and Cochrane library from 1 January 2005 to 30 June 2021 was conducted. RCTs that compared haemostatic agents with placebo for the treatment of spontaneous patients with ICH with high-risk haemorrhage growth were included. The primary endpoint was haematoma expansion at 24 hours. Other major endpoints of interest included 90-day functional outcome and mortality. Results: The meta-analysis included four RCTs that randomised 2666 patients with ICH with high-risk haemorrhage growth. Haemostatic therapy reduced the rate of haematoma expansion at a marginally statistically significant level when compared with placebo (OR 0.84; 95% CI 0.70 to 1.00; p=0.051). Subgroup analysis for patients with black hole sign on CT revealed a significant reduction of haematoma expansion with haemostatic therapy (OR 0.61; 95% CI 0.39 to 0.94; p=0.03). However, both the primary analysis and subgroup analyses showed that haemostatic therapy could not reduce the rate of poor functional outcome (modified Rankin Scale >3) or death. Conclusions: Haemostatic therapy showed a marginally significant benefit in reducing early haematoma expansion in patients with high-risk spontaneous ICH predicted by markers on CT scan. However, no significant improvement in functional outcome or reduction of mortality was observed.